VIRTUAL SCREENING AND BIOLOGICAL EVALUATION OF AVIAN ERYTHROBLATOSIS VIRUS E26 ONCOGENE (ETS-1) INHIBITOR - S. Mehreen; A. Javeed; M. Ashraf; A. Riaz; M. Hussain; L. Shakir (Journal of Animal and Plant Sciences, 2014)
This study was designed to identify and characterize novel inhibitor of Ets-1 by using virtual screening approach combined with biological evaluation of anti-angiogenic ability of compound. Virtual screening of Indian plant anticancer compound database was performed against phosphorylation site (Threonine-38) of Ets-1 by Auto Dock 4.02. A compound with lowest energy score (-4.28kcal/mol) was selected. Biological activity of compound obtained from virtual screening was further evaluated by performing chick chorioallantoic membrane (CAM) assay. Different concentrations (0.5 %, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 6%, and 12%) of aqueous extract of saffron plant containing screened compound (Picrocrocin) were applied to CAMs and scanning probe image processor was used for quantification of membrane vasculature. Results showed that application of 2% and 3% concentration of extract showed reduction in diameter of blood vessels, decrease in abbot curve area and reduction in surface roughness parameters. This study revealed a potential inhibitor of Ets-1 and anti-cancer mechanism of saffron.
Keywords: Virtual screening; angiogenesis; cancer; chick chorioallantoic membrane